Pemanfaatan Diskusi Berdasarkan Kasus Sebagai Ujian Formatif Dalam Program Pendidikan Dokter Spesialis Patologi Anatomik Fakultas Kedokteran Universitas Indonesia - Saraswati, Meilania; Simadibrata, Marcellus; Mustika, Rita (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Background: Postgraduate program for Anatomical Pathology Specialist in Faculty of Medicine Universitas Indonesia use competence-/outcome-based curriculum approach. However, until now, the program has not yet adopted a structured, recorded, formative workplace-based assessment, for example, case-based discussion.Method: This was an explorative qualitative research regarding the use of formative assessment case-based discussion during educational process in postgraduate program for anatomical pathology specialist in FMUI. Interview and focused group discussion to the program manager, teaching staff and the residents were performed. Teaching staff was asked to perform three times case-based discussion (CbD) formative assessment toward the resident. Post-intervention, interview and focused group discussion to the staf and resident were conducted. Result: The staffs and residents of Anatomical Pathology Specialist Program of FMUI showed positive response toward CbD formative assessment. CbD formative assessment enabled deeper discussion between the staffs and residents regarding establishing diagnosis. The staffs were able to monitor the residents’ learning process and giving specific feedback toward the residents. The residents were able to learn about a case in a more comprehensive way and acquiring specific feedback and summative assessment simulation.Conclusion: CbD formative assessment is useful in the process of acquiring competence in diagnosis in a postgraduate education that uses competence- or outcome-based curricula.